Actividad antimicrobiana del aceite esencial de las hojas de Peperomia dolabriformis Kunth frente a Escherichia coli y Candida albicans - Alfaro TTito, Bertha Mirella (2018)
The objective of the present study was to evaluate the antimicrobial activity of the essential oil of the leaves of Peperomia dolabriformis Kunth against Escherichia coli and Candida albicans. The leaves were collected from the Coastal Hills of Cerro Campana in the district of Huanchaco, from which the essential oil was obtained by the hydrodistillation method. The evaluation of the in vitro antimicrobial activity was carried out by the well diffusion method of modified Kirby-Bauer agar. The essential oil from the leaves of Peperomia dolabriformis presented an antimicrobial effect in vitro against Escherichia coli (ATCC 25922) and Candida albicans (ATCC 90028), at concentrations of 0.5%, 1.0%, and 2.5%, obtaining averages of inhibition halos of 14.06 mm; 15.14 mm; 17.36 mm against Escherichia coli and 12.78 mm; 14.02 mm; 15.72 mm against Candida albicans; thus, the percentages of inhibition obtained were 51.05%, 54.97% and 63.03% for Escherichia coli and 42.43%, 46.55% and 52.19% for Candida albicans, at concentrations of 0.5%, 1.0% and 2.5% respectively; showing higher percentages of inhibition in E. coli (63.03%) and C.albicans (52.19%) at the concentration of 2.5%, and with a statistically significant difference (p <0.05).